An overview and single-arm meta-analysis of immune-mediated adverse events following COVID-19 vaccination - Yang, Donghua; Tian, Jinhui; Shen, Caiyi; Li, Qin (Frontiers in Pharmacology, 2024)
We conducted an overview to assess immune adverse effects associated with the COVID-19 vaccine, guiding safer choices and providing evidence-based information to clinicians. Methods: Forty-three studies on adverse effects of vaccines were reviewed from PubMed, Embase, and Web of Science. Single-arm meta-analyses estimated summary effects, incidence, presentation, etc. An overview using single-arm meta-analysis and reported the findings following the guidelines outlined in the 'Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA). specifically focusing on myocarditis and thrombosis. After screening 2591 articles, 42 studies met the inclusion criteria. Methodological quality was evaluated using AMSTAR 2. Disagreements were resolved via consensus. Data analysis utilized a random-effects model in R software to estimate incidence rates of selected adverse events. Results: After removing 1198 duplicates and screening out irrelevant articles from a total of 2591, we included 42 studies. Adverse reactions to vaccinations include myocarditis, thrombosis, skin reactions, GBS, etc.thrombosis and myocarditis are the most dangerous diseases associated with vaccination.Myocarditis occurred in 6% of Vector vaccine recipients, compared to 61% of mRNA vaccine recipients. Thrombosis was more common after Vector vaccination (91%) than after mRNA vaccination (9%). Furthermore, eight studies conducted anti-PF4 antibody tests and yielded a positivity rate of 67%. Meta-analysis showed that among all patients with VITT, CVST occurred in 66% , and ICH occurred in 43%. The rates of deep vein thrombosis and pulmonary thromboembolism in vaccinated patients were 13% and 23%, respectively, with a pooled case fatality rate of 30%. Conclusions:The results of this overview indicate the majority of adverse reactions are self-limiting and require minimal intervention, while rare occurrences such as myocarditis and thrombosis pose a potentially fatal threat.